Using mobile devices for learning in clinical settings: A mixed‐methods study of medical student, physician and patient perspectives. (22nd September 2015) - Scott, Karen M.; Nerminathan, Arany; Alexander, Shirley; Phelps, Megan; Harrison, Amanda
Abstract: This study was conducted with medical students, physicians, patients and carers in a paediatric and an adult hospital to determine use of mobile devices for learning, and beliefs and attitudes about others' use. Awareness of ethical, patient privacy and data security concerns was explored. The research was conducted using a mixed‐methods sequential explanatory design through survey and focus groups for students and physicians, and a separate survey for patients and carers. Each arm of the study was analysed individually, followed by integration of quantitative and qualitative data, which are the subject of this paper. Interpretation of the integrated student and physician quantitative data highlighted that both groups used mobile devices for information verification, organisation and communication, and these represented the best uses of mobile devices; the worst aspects of mobile devices involved Internet access difficulties. Interpretation of the integrated student and physician qualitative data highlighted that students and physicians made individual decisions about their use of mobile devices, despite some existing policies. Integration of all data from all arms of the study identified the benefits of using mobile devices and concerns about distraction. For many students and physicians, the benefits of using mobile devices for learning at the patient bedside outweigh the possible risks. As society grapples with norms governing appropriate use of mobile devices, many are devising their own rules to aid learning in clinical settings.